Design of Monitoring System of Gas and Environment of Coal Mine Based on CAN Bus - LI Tao; LI Hui (Gong-kuang zidonghua, 2011)
In order to solve problems of non-real time and higher error rate caused by artificial detecting mode of traditional gas monitoring methods of coal mine underground, the paper put forward a design scheme of monitoring system of gas and environment of coal mine based on CAN bus according to characteristics of complex production environment, long transmission distance and wide monitoring range in coal mine. The system takes AT89S52 single-chip microcomputer as core of lower computer system and can automatically monitor environment parameters of temperature, wind speed and gas concentration of underground by use of technologies of 1-wire bus and multi-sensor, then real-timely transmits the parameters to upper computer through CAN bus. The experimental result showed that the system has high stability, reliability and anti-interference ability.